Analisis Pengaruh Customer Trust Terhadap Keputusan Menggunakan Mobile Banking Melalui Perceived Risk Sebagai Variabel Intervening - Hana Nafisah; Ahmad Amin Dalimunte; M. Ikhsan Harahap (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the Analysis of the Effect of Customer Trust on the Decision to Use Mobile Banking Through Perceived Risk as an Intervening Variable (Case Study on Mobile Banking Application Users at UIN North Sumatra Students). This study uses a quantitative approach. In this study, a questionnaire was used to collect data, and 100 students at UIN Sumatra Utara were selected as a sample using a purposive sampling method. Data analysis in this research is quantitative data analysis. Statistical tests known as the T-test, F-test, and the coefficient of determination R2 are all components of this analysis, as are the path analysis tests. Based on the research analysis, it can be concluded that customer trust has a positive and significant effect on perceived risk, customer trust has a positive and significant effect on the decision to use, perceived risk has a positive and significant effect on the decision to use, customer trust has a positive and significant effect on the decision to use through perceived risk as intervening variable. This means that a high perceived risk in accordance with customer trust will lead to a high decision to use the mobile banking application. This result is important for Islamic banking to minimize the risks that will be felt. Through breakthroughs to improve the security of the mobile banking system, thereby maintaining customer trust which will have an impact on the decision to use mobile banking services.